2019
DOI: 10.1007/s10067-019-04535-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and effectiveness of tocilizumab in patients with rheumatoid arthritis and inadequate responses to csDMARDs and/or TNF inhibitors: an open-label study close to clinical practice

Abstract: Objective To assess the long-term safety, tolerability, and effectiveness of tocilizumab (TCZ) as monotherapy or in combination with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) in clinical practice in patients with moderate to severe rheumatoid arthritis (RA). Methods Patients in the 24-week, open-label ACT-SURE study who had at least a moderate EULAR response by week 24 and were from a participating country were eligible for this long-term extension (LTE); the patients continued to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The reported AEs associated with tocilizumab in our study were consistent with its known safety profile in RA 36–38 . The long‐term safety profile of tocilizumab (mean treatment duration, 2.4 years) from several phase III trials and open‐label extensions did not demonstrate an increase in serious or treatment‐related AEs, and the data were overall consistent with those of post‐marketing trials and clinical experience 39 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The reported AEs associated with tocilizumab in our study were consistent with its known safety profile in RA 36–38 . The long‐term safety profile of tocilizumab (mean treatment duration, 2.4 years) from several phase III trials and open‐label extensions did not demonstrate an increase in serious or treatment‐related AEs, and the data were overall consistent with those of post‐marketing trials and clinical experience 39 .…”
Section: Discussionsupporting
confidence: 85%
“…The reported AEs associated with tocilizumab in our study were consistent with its known safety profile in RA. [36][37][38] The long-term safety profile of tocilizumab (mean treatment duration,…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a significantly higher proportion of patients achieved clinical remission at 24-week follow-up. Other prospective studies also reported that patients with RA showed a better clinical response at 24-week follow-up [49][50][51].…”
Section: Discussionmentioning
confidence: 81%
“…It is characterized by inflammation of the synovium, which often results in irreversible joint damage if left untreated. 1,2 Pro-inflammatory cytokines like tumour necrosis factor (TNF), Interleukin 6 (IL-6) and Interleukin 1(IL-1) have been implicated in pathogenesis. 3,4 TNF inhibitors have a high risk of tuberculosis (TB) reactivation, which is especially relevant in TB-endemic areas like ours.…”
Section: Introductionmentioning
confidence: 99%